“Lost in translation?” Animal research in the era of precision medicine - Hamideh Frühwein; Norbert W. Paul (Journal of Translational Medicine)
Abstract Preclinical animal research has long been a cornerstone in evaluating the efficacy, toxicity, and safety of potential drug treatments before they proceed to human clinical trials. However, given the intricate nature of human physiology and the complexities of diseases such as cancer, this paper critically examines the role of animal experimentation in translational research, both from epistemological and ethical viewpoints. We argue that the ethical obligation to protect animals extends beyond their instrumental value for human benefit; it is rooted in the intrinsic value of their well-being. Consequently, we advocate for a paradigm shift in medical research: the adoption of new approach methodologies (NAMs) not merely as supplementary tools but as complete replacements for animal use in medical studies. In this context, replacement emerges as the key principle—an imperative that should be prioritized over all other considerations.